Titanica - Low, Stephen; Miramax Films; Speedy Video Distributors Sdn. Bhd. ([New York] : Miramax Films (publisher) ; Malaysia : Speedy Video Distributors Sdn. Bhd. (distributor), 2002)
Reveals the clearest motion pictures ever captured of the Titanic. Witness startling images of the long-lost ruin contrasted with never-before-seen 1912 archival photos showing her in all her splendor. Relive the memories of two survivors, an exclusive interview with Frank Goldsmith and the poignant recollections of Eva Hart
Title from title screen
Acquisition for KPI (Kelab Pencinta Ilmu)
Editor, James LAhti ; executive producer, Andre Picard, Dr. Joseph Macinnis
Narration : Leonard Limoy
Keywords: Titanic (steamship); Shipwrecks -- North Atlantic Ocean -- History; Ships